Pengaruh Model Problem Based Learning (PBL) Terhadap Berpikir Kritis Di Kelas IV UPT SD Negeri 06 Pasar Taratak Pesisir Selatan - Martha, Alfroki (Jurnal Riset Pendidikan Dasar Dan Karakter, 2023)
This research is motivated by the low critical thinking skills of students which is caused by teachers who rarely ask students, and the questions asked by teachers do not make students think critically, besides that teachers make children get bored quickly. This research aims to determine the influence of the Problem Based Learning model. (PBL) on students' critical thinking skills in class IV UPT SDN 06 Pasar Taratak Pesisir Selatan. This type of research is an experiment with a quasi-experimental research design. This type of research is an experiment with a quasi-experimental research design. The results of this research show that t = 4.442 and t table = 1.687 and the significance level is 5%. Based on the test tcount>t table (4.442 > 1.687), the hypothesis or H₁ is accepted. From the research results, it is proven that the problem based learning (PBL) model has a significant influence on students' critical thinking skills in class IV students at UPT SDN 06 Pasar Taratak Pesisir Selatan.